A study of entrepreneurial reaction patterns based on micro analyses of the Bureau for Economic Research survey data - Marais, D. J.(Daniel Jacobus) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (DBA) -- University of Stellenbosch, 1995.